Zizek and performance - Chow, Broderick; Mangold, Alex (New York Palgrave Macmillan, 2014)
Slavoj Zizek is a cultural phenomenon. His writings have influenced the way we think about politics, psychoanalysis, and a range of cultural issues in our increasingly volatile political and economic climate. This is the first collection to relate explicitly his thoughts on neoliberalism, globalisation, social change and subjectivity to the theory and practice of theatre and performance. Are there common grounds between Zizek's performative persona, his writing style, and performative and theatrical events? Can theatre and performance theories and practices shed some more light on the 'Elvis of cultural theory' and his often controversial work? This volume features 16 critical essays that examine a truly eclectic range of performance makers, events, and moments - from Wagner's Parsifal to Daniel Radcliffe, from Forced Entertainment to Hollywood dance. It concludes with a new text from Zizek himself, as he turns, for the first time, his gaze to performance.